Peran Guru PKn dalam Membentuk Wawasan Kebangsaan Peserta Didik di Era Globalisasi - Sri Wenni; Nadia Kezia Situmeang; Sardame Hotmauli Sitompul; Febry Nurhayati; Waliyul Maulana Siregar (Bhinneka: Jurnal Bintang Pendidikan dan Bahasa, 2024)
The era of globalization, which is marked by the increasingly open flow of information and culture from various parts of the world, also has its own impact on Indonesia's young generation. On the one hand, globalization opens up horizons of insight and knowledge, but on the other hand, it can erode national values and national identity if not addressed wisely. This study aims to analyze the role of Civic Education (Civics Education) teachers in shaping students' national insight amidst the swift flow of globalization. By using qualitative method through observation, interview, and document study, this research examines learning strategies and approaches applied by Civics Education teachers in instilling national values. The results show that Civics teachers have a central role in fostering students' national awareness and insight, including through the use of contextual learning media, the application of student-centered learning methods, and the integration of Pancasila and Unity in Diversity values in every learning material. In addition, Civics teachers also act as role models in practicing national values in daily life. This study recommends the need to increase the competence and awareness of Civics teachers in facing the challenges of globalization, as well as support from all education stakeholders in building the character and national insight of Indonesia's young generation.